2022
DOI: 10.1097/jte.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Development of Burnout in Physical Therapist Students and Associated Factors: A Study During COVID-19

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In a previous study, satisfaction with the level of support from faculty had a significant influence on the development of burnout, with the odds of developing burnout increasing by 1.421 for each 1-unit decrease in satisfaction with the level of support from faculty. 23 Similar results were found among year 1 and 2 medical students. 18 Feeling supported by faculty members and the DPT cohort may boost well-being and defend against the development of burnout in DPT students.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In a previous study, satisfaction with the level of support from faculty had a significant influence on the development of burnout, with the odds of developing burnout increasing by 1.421 for each 1-unit decrease in satisfaction with the level of support from faculty. 23 Similar results were found among year 1 and 2 medical students. 18 Feeling supported by faculty members and the DPT cohort may boost well-being and defend against the development of burnout in DPT students.…”
Section: Discussionsupporting
confidence: 76%
“…17,19,21,22 e results from a previous study assessing burnout in DPT students indicated that perceived stress, level of resilience, satisfaction with the level of support from faculty, and satisfaction with the overall learning environment at the DPT school may influence the development of burnout in DPT students. 23 Nearly all published studies assessing burnout and factors related to the development of burnout are quantitative in nature and frequently consist of outcome measures and surveys. Speaking directly with students may shed light on their perception of burnout and what factors they feel affect their well-being while in DPT school; these perceptions might not be captured by surveys.…”
Section: Jennifer Ellison Is An Associate Professor In Thementioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8] Studies have shown that health professional students experienced a wide array of adverse ramifications during the pandemic. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Findings show that the pandemic influenced levels of psychosocial and economic hardships. [21][22][23][24][25][26] Specifically, research indicates that DPT students withstood increased stress, burnout, fatigue, anxiety, and depression, decreased quality of life, financial hardship, lower program satisfaction, and sleep disturbances.…”
Section: Review Of Literaturementioning
confidence: 99%